The Diagnostic Value of Chemokine/Chemokine Receptor Pairs in Hepatocellular Carcinoma and Colorectal Liver Metastasis. (May 2019) - Jiao, Xiaolei; Shu, Guiming; Liu, Hui; Zhang, Qin; Ma, Zhe; Ren, Chaoyi; Guo, Hongsheng; Shi, Jingxiang; Liu, Junguo; Zhang, Chuanshan; Wang, Yijun; Gao, Yingtang
Chemokines and their receptors have been proposed to play important roles in tumor progression and metastasis. To investigate their roles in the progression of primary and metastatic malignant liver tumors and their prognosis, we compared expression profiles of CXCL12/CXCR4, CCL20/CCR6, and CCL21/CCR7 in hepatocellular carcinoma (HCC) and colorectal liver metastases (CRLM). Immunohistochemistry was used to analyze the expression levels of the chemokine/chemokine receptor pairs in 29 HCC and 11 CRLM specimens and adjacent non-cancerous tissues, and correlations with clinicopathological variables and overall survival were determined. CCL20/CCR6 expression was higher in HCC than in adjacent non-cancerous tissues. High CCR6 expression in HCC was negatively associated with 5-year survival rate and was an independent prognostic factor for overall survival of HCC patients, whereas differences were not observed between CRLM and adjacent tissues. Furthermore, significantly higher expression of CCL21/CCR7 was found in CRLM than in HCC. In summary, the CCL20/CCR6 axis was elevated in HCC but not in CRLM, whereas the CCL21/CCR7 axis was elevated in CRLM but not in HCC.